A comparison of the academic achievements of The Pre-Diploma Science (MDAB) students of 2014, 2015, and 2016 as well as its relation to the second quality objective of UiTM Cawangan Negeri Sembilan / Nur Jannah Azman and Mazliyana Zainal Arifin - Azman, Nur Jannah; Zainal Arifin, Mazliyana (Universiti Teknologi MARA, Negeri Sembilan, 2017)
The MDAB programme was founded by UiTM to assist students who come from the low-income group but are interested in continuing their studies and meet the requirements set by the University for them to further their studies in the Pre-Diploma level. Since it was set up in 2010, no specific studies were done to see how far the programme had succeeded in helping these students to further their studies to a higher level. Hence, an analysis was done on the students' achievements and compared from the year 2014, 2015, and 2016 to identify whether they meet the Second Quality Objective of UiTM Cawangan Negeri Sembilan. Based on the analysis done on the academic performance by the Pre-Diploma Science (MDAB) students in UiTM Cawangan Negeri Sembilan, it can be concluded that the commitment by the management especially the Academic Affairs Division UiTM Cawangan Negeri Sembilan, Director of MDAB, Head of Academic MDAB, as well as the Management Office of MDAB, UiTM Shah Alam , played an essential role in maintaining the quality and academic performance of the students.